Circulating cell-free-DNA concentration is a good biomarker for diagnosis of colorectal cancer in Mexican patients: Circulating cell-free DNA in colorectal cancer - Saucedo-Sariñana, Anilú Margarita; Lugo-Escalante, Carlos Roberto; Barros-Núñez, Patricio; Marín-Contreras, María Eugenia; Pineda-Razo, Tomas Daniel; Mariscal-Ramírez, Ignacio; Gallegos-Arreola, Martha Patricia; Rosales-Reynoso, Mónica Alejandra (Cellular and Molecular Biology, 2022)
Colorectal cancer (CRC) is the third most common cancer in the world. Overall survival is related to clinical stage: more advanced stages show lower survival rates; therefore, they need to be monitored regularly with new, less invasive and more specific biomarkers. The concentration and integrity index of circulating cell-free DNA (ccfDNA) have been proposed as potential diagnostic and prognostic biomarkers for CRC, however, inconsistent results are still observed in different reports. Here we analyze these potential CRC biomarkers in a Mexican population. In this study, 124 patients with sporadic CRC and 37 healthy individuals were examined as a reference group. The ccfDNA was isolated from plasma samples of all included subjects. The ccfDNA concentration was determined by fluorometry and the integrity index (ALU247/ALU115 ratio) by quantitative PCR amplification (qPCR) of ALU sequences. The results show that ccfDNA concentration was higher in CRC patients than in the reference group (P=0.001). The integrity index showed no significant differences between these groups (P=0.258), except for histological type (P=0.012). A higher ccfDNA concentration was also associated with patients younger than 50 years (P=0.030). The ccfDNA concentration showed significant discriminatory power (AUC: 0.854, C.I.: 0.78-0.92, P=0.001) between patients and the reference group and between tumor-node-metastasis (TNM) stages. In conclusion, ccfDNA concentration proves to be a good diagnostic biomarker for CRC patients, whereas the integrity index did not show diagnostic utility.